Implementation of the Differentiated Learning Model Based on Banyumasan Local Wisdom at Madrasah Ibtidaiyah Negeri 1 Banyumas - Mayasari, Novi; Aunurrokhim, Khisni (Institut of Shanti Bhuana, 2024)
This research examines the implementation of a differentiated learning model based on Banyumasan local wisdom in the State Madrasah Ibtidaiyah (MI) of Banyumas Regency. The aim of this research is to describe and analyze the implementation of a differentiated learning model based on local Banyumasan wisdom at Madrasah Ibtidaiyah 1 Banyumas. This type of research is field research. Data collection techniques are interviews, observation and documentation. Data validity techniques use source triangulation and technical triangulation. Data analysis techniques include collecting data, reducing data, presenting data and drawing conclusions. The results of the research show that the implementation of the differentiated learning model based on Banyumasan local wisdom at MIN 1 Banyumas, starting from planning, implementation and evaluation, has been carried out in accordance with the differentiated learning concept guidelines in the independent curriculum and is linked to the local wisdom of Banyumas culture. At the learning planning stage, the teacher analyzes students' learning readiness through a diagnostic questionnaire to determine the characteristics and needs of students, then the results of the analysis of student needs are used as a reference in compiling open modules. At the implementation stage, the differentiated learning model based on Banyumasan local wisdom has described process differentiation with a variety of methods according to students' needs, differentiation of science material content by linking Banyumas Begalan cultural wisdom, and differentiation of learning products, one of which is the IPAS element LKPD which is linked to Begalan local cultural wisdom. Banyumas. The evaluation stage is carried out by the teacher providing test or non-test evaluation instruments by providing time differences according to the student's ability level.